Growth hormone promotes neurite growth of spiral ganglion neurons. Issue 8 (23rd May 2018) - Gabrielpillai, Jennis; Geissler, Christin; Stock, Belinda; Stöver, Timo; Diensthuber, Marc
Abstract : Intact spiral ganglion neurons are a specific requirement for hearing rehabilitation in deaf patients by cochlear implantation. Neurotrophic growth factors have been proposed as effective tools to protect and regenerate spiral ganglion neurons that are degenerated in the majority of patients suffering from hearing loss. Here, we show that growth hormone (GH), a pleiotropic growth factor whose neurotrophic role in the inner ear is still unclear, significantly increases neurite extension, as well as neuronal branching, in spiral ganglion cell cultures derived from early postnatal rats. Our data suggest that GH can act as a potent neurotrophic factor for inner ear neurons, which specifically promotes neurite growth. These effects might be elicited in a direct way or, alternatively, by induction of other growth factors that account for the observed neurotrophic effects. Thus, we conlude that GH might represent a novel candidate for the treatment of neurodegeneration in the hearing-impaired inner ear that has the potential to ultimately improve the performance and outcome of modern auditory implants.